MIS-C pathogenesis: immune dysregulation & viral triggers - Xu, Tiantian; Zhang, Jiamin; Hou, Xiangyuan; Xie, Xinyu; Qi, Junye; Wang, Changbing; Yan, Yuqing; Kuang, Lu; Zhu, Bing (Frontiers in Immunology, 2025)
Multisystem Inflammatory Syndrome in Children (MIS-C) is a serious condition emerging during the COVID-19 pandemic, strongly associated with prior SARS-CoV-2 infection. Characterized by systemic inflammation affecting multiple organs, MIS-C presents a complex clinical picture including fever, gastrointestinal distress, cardiac dysfunction, and neurological manifestations. Although its exact pathogenesis remains incompletely understood, immune dysregulation is recognized as a central mechanism. This review examines current understanding of MIS-C pathogenesis, focusing on immune dysfunction and viral triggers, particularly SARS-CoV-2. We analyze both innate and adaptive immune responses, cytokine storm dynamics, molecular mimicry, and virus-induced inflammatory cascades. Additionally, we discuss potential immunomodulatory therapeutic strategies and identify future research directions to improve MIS-C management and treatment outcomes.